Linking genetic, morphological, and behavioural divergence between inland island and mainland deer mice - Miller, Joshua M.; Garant, Dany; Perrier, Charles; Juette, Tristan; Jameson, Joël W.; Normandeau, Eric; Bernatchez, Louis; Réale, Denis (My University, 2022)
The island syndrome hypothesis (ISH) stipulates that, as a result of local selection pressures and restricted gene flow, individuals from island populations should differ from individuals within mainland populations. Specifically, island populations are predicted to contain individuals that are larger, less aggressive, more sociable, and that invest more in their offspring. To date, tests of the ISH have mainly compared oceanic islands to continental sites, and rarely smaller spatial scales such as inland watersheds. Here, using a novel set of genome-wide SNP markers in wild deer mice (Peromyscus maniculatus) we conducted a genomic assessment of predictions underlying the ISH in an inland riverine island system: analysing island-mainland population structure, and quantifying heritability of phenotypes thought to underlie the ISH. We found clear genomic differentiation between island and mainland populations and moderate to high marker based heritability estimates for overall variation in traits previously found to differ in line with the ISH between mainland and island locations. FST outlier analyses highlighted 12 loci associated with differentiation between mainland and island populations. Together these results suggest that the island populations examined are on independent evolutionary trajectories, the traits considered have a genetic basis (rather than phenotypic variation being solely due to phenotypic plasticity). Coupled with the previous results showing significant phenotypic differentiation between island and mainland groups in this system, this study suggests that the ISH can hold even on a small spatial scale.
Keywords: island syndrome; heritability; FST outlier; deer mice; ddRAD